The Study of Heart Rate and Respiratory Rate during the Semen Collection in Two Species of Hornbill - Kanatiyanont, Nathavut; Noimoon, Sakhon; Pinyopummin, Anuchai (Journal of Mahanakorn Veterinary Medicine, 2018)
The monitoring of vital signs during anesthesia is important for animal safety. The extrinsic stimulations may affect to vital signs during anesthesia. This study was performed under anesthesia in two species of hornbill (Oriental pied hornbill; Anthracoceros albirostris and Great hornbill; Buceros bicornis). The respiration rate and heart rate were monitored. The data were collected during the semen collection process. During the process, the difference voltages were applied to both hornbills. The results were showed. The average of heart rate in the Oriental pied hornbill (175.18 ± 4.9 beats/minute) was higher than the Great hornbill (152.72 ± 3.5 beats/minute). The average of respiratory rate in the Great hornbill (23.74 ± 3.1 breaths/minute) was higher than the Oriental pied hornbill (20.28 ± 0.7 breaths/minute). Heart rate and respiratory rate during the semen collection in each series were statistical analysis. There is no significantly difference of heart rate and respiratory rate in each series (P>0.05). In conclusion, the semen collection by electro-stimulation had no effect to vital signs of both hornbills. These results will be useful to anesthesia in others hornbill species during the semen collection.